2013
DOI: 10.1016/j.juro.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Online Reviews of 500 Urologists

Abstract: We advise physicians and patients to be aware that most urologists are rated on at least 1 physician review website, and while most ratings and reviews are favorable, composite scores are typically based on a small number of reviews and, therefore, can be volatile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 8 publications
10
74
0
Order By: Relevance
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 82%
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 82%
“…Using a modification of methodologies detailed by Ellimoottil et al [3] and Gray et al [4], we selected five "popular physician review websites" from which to collect information for each radiologist: HealthGrades.com, HealthcareReviews.com, RateMDs.com, Kudzu.com, and Yelp.com. Over a several-month period in 2014, we manually searched each site for all 1,000 selected radiologists that matched NCH SAF physician demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, a total of 32.4% of all obstetrician-gynecologists had been reviewed online, in contrast to only 6.6% of radiologists, anesthesiologists, and pathologists (collectively grouped as "other specialists"). That trend toward more online physician ratings seems to be gaining momentum; recent multiwebsite studies indicate that most urologists [3] and internists [4] are now profiled on such sites.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have attempted to correlate factors associated with higher online patient ratings of individual physicians, such as physician sex, years in practice, medical specialty, insurance status, volume of online patient ratings, geographic region, and academic position. 5,8,11 Lopez et al 12 stated that patient reviews of physicians were affected by office staff, access to care, and convenience.…”
mentioning
confidence: 99%